2013
DOI: 10.1093/aob/mct064
|View full text |Cite
|
Sign up to set email alerts
|

Variation in nutrient-acquisition patterns by mycorrhizal fungi of rare and common orchids explains diversification in a global biodiversity hotspot

Abstract: These results suggest that OMF can differentiate between niches (micro-niche specialization) in a constrained, highly resource-limited environment such as the SWAFR. Phosphorus is the most limited macronutrient in SWAFR soils and the ability to access phytate by OMF indicates a characterizing functional capacity of OMF from the SWAFR. Furthermore, compared with OMF isolated from the rare D. elastica, OMF associating with the common P. recurva produced far greater biomass over a wider variety of nutritional sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
67
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(78 citation statements)
references
References 57 publications
11
67
0
Order By: Relevance
“…Nurfadilah et al . () reported different N source preference in orchid mycorrhizal fungi because isolates in the genus Tulasnella could use ammonium but not nitrate as inorganic N forms, whereas isolates in the genus Ceratobasidium could use both ammonium and nitrate. Growth of T. calospora isolate AL13/4D on different N sources confirmed a preference for ammonium and organic N sources, like other cultivable orchid mycorrhizal fungi (Hadley & Ong, ; Nurfadilah et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Nurfadilah et al . () reported different N source preference in orchid mycorrhizal fungi because isolates in the genus Tulasnella could use ammonium but not nitrate as inorganic N forms, whereas isolates in the genus Ceratobasidium could use both ammonium and nitrate. Growth of T. calospora isolate AL13/4D on different N sources confirmed a preference for ammonium and organic N sources, like other cultivable orchid mycorrhizal fungi (Hadley & Ong, ; Nurfadilah et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…This reinforces the nutrient access studies by Nurfadilah et al . () and clearly raises the prediction that some orchid–OMF combinations will be more beneficial than others and that it will be habitat dependent.…”
Section: Orchid Mycorrhizal Fungus Identity and Orchid Distribution Amentioning
confidence: 94%
“…Fungi associated with orchids have diverse nutritional needs (Nurfadilah et al ., ), but it is not currently thought that they need to associate with or are necessarily co‐distributed with orchids. A few studies have demonstrated or intimated that orchids may contribute carbon to their fungi (Cameron et al ., , ; Hynson et al ., ; Ogura‐Tsujita et al ., ; Liebel et al ., ), suggesting that association with the orchid might benefit the fungus.…”
Section: Orchid Mycorrhizaementioning
confidence: 99%
See 1 more Smart Citation
“…The first step in this direction has been taken by Nurfadilah et al . (), who examined the nutrient acquisition abilities of fungi associated with several species of Australian orchids. They found that fungi that associated with rare, habitat‐specialist orchids were able to utilize a narrower range of nutrient sources than those that associated with more widespread orchids, suggesting a possible mechanism for the connection between mycorrhizal fungus distribution and abundance and orchid rarity.…”
Section: Local‐scale Dynamicsmentioning
confidence: 99%